Bone‐Targeted Bortezomib Inhibits Bortezomib‐Resistant Multiple Myeloma in Mice by Providing Higher Levels of Bortezomib in Bone. (22nd January 2022) - Tao, Jianguo; Srinivasan, Venkat; Yi, Xiangjiao; Zhao, Yingchun; Zhang, Hengwei; Lin, Xi; Zhou, Xichao; Boyce, Brendan F; Villalta, Peter W; Ebetino, Frank H; Ho, Koc Kan; Boeckman, Robert K; et al.
ABSTRACT: Limited treatment options exist for cancer within the bone, as demonstrated by the inevitable, pernicious course of metastatic and blood cancers. The difficulty of eliminating bone‐residing cancer, especially drug‐resistant cancer, necessitates novel, alternative treatments to manipulate tumor cells and their microenvironment, with minimal off‐target effects. To this end, bone‐targeted conjugate (BP‐Btz) was generated by linking bortezomib (Btz, an anticancer, bone‐stimulatory drug) to a bisphosphonate (BP, a targeting ligand) through a cleavable linker that enables spatiotemporally controlled delivery of Btz to bone under acidic conditions for treating multiple myeloma (MM). Three conjugates with different linkers were developed and screened for best efficacy in mouse model of MM. Results demonstrated that the lead candidate BP‐Btz with optimal linker could overcome Btz resistance, reduced tumor burden, bone destruction, or tumor metastasis more effectively than BP or free Btz without thrombocytopenia and neurotoxicity in mice bearing myeloma. Furthermore, pharmacokinetic and pharmacodynamic studies showed that BP‐Btz bound to bone matrix, released Btz in acidic conditions, and had a higher local concentration and longer half‐life than Btz in bone. Our findings suggest the potential of bone‐targeted Btz conjugate as an efficacious Btz‐resistant MM treatment mechanism. © 2021 American Society for Bone and Mineral Research (ASBMR).